Sire evaluation models for estimating breeding values of Mehsana buffaloes - SATHWARA, R N; GUPTA, J P; CHAUDHARI, J D; PRAJAPATI, B M; SRIVASTAVA, A K; CHAUHAN, H D; PATEL, P A (The Indian Journal of Animal Sciences, 2019)
First lactation data on 7,782 Mehsana buffaloes sired by 184 sires maintained at Dudhsagar Research and Development Association, Dudhsagar Dairy, Mehsana over a period of 24 years (1989–2012) were used to estimate least-squares means (LSM) and breeding value of the first lactation fat yield (FLFY) and average fat percentage (AFP) using univariate and bivariate models with the help of WOMBAT software. The effectiveness of different sire evaluation models using FLFY and AFP were compared on the basis of error variance, coefficient of determination (CV%), R2-value, AIC, BIC and Spearman’s rank correlation. The average estimate of FLFY and AFP was 135.04±0.57 kg and 7.11±0.11% in Mehsana buffaloes. These estimates were significantly affected by period and season of calving, and age at first calving group. The average expected breeding value of Mehsana buffalo bulls for FLFY and AFP were 133.24 kg and 7.14% using sire model (BLUP-SM), 135.71 kg and 7.22% using univariate animal model (BLUP-U-AM) and 133.23 kg and 7.14% from bivariate animal model (BLUP-B-AM), respectively for FLFY and AFP. The spearman’s rank correlation indicated similarity of rankings by BLUP-U-AM and BLUPB- AM. Animal model had a wider range of breeding values indicating the greater differentiating ability of the model. Based on error variance, AIC, BIC, R2 and CV; animal model was found to be superior in comparison to sire model.